CircNF1 promotes gastric cancer metastasis by stabilizing HMGA2 mRNA through IGF2BP1 interaction - Sun, Yingying; Ge, Yanli; Xia, Zhiyu; Guo, Cheng; Zhang, Junjie; Wang, Zhirong; Wang, Zhe (Frontiers in Immunology, 2026)
IntroductionGastric cancer (GC) is the fifth most common malignancy worldwide, with metastasis being the primary cause of mortality. Although circular RNAs (circRNAs) are implicated in GC pathogenesis, their specific roles in metastasis remain unclear. This study was designed to investigate the functional significance and underlying molecular mechanisms of circNF1 in GC metastasis.MethodsThe expression of circNF1 was assessed in GC tissues and paired adjacent normal tissues using in situ hybridization, and its clinical relevance was evaluated via Cox regression analysis. Functional characterization was performed using transwell migration assays and in vivo metastatic mouse models to determine the effects of circNF1 overexpression or knockdown on GC cell motility and lung metastasis. Mechanistic investigations included molecular interaction studies to explore the association between circNF1 and IGF2BP1, as well as transcriptional regulation assays to identify the upstream regulator of circNF1 biogenesis.ResultsOverexpression of circNF1 significantly enhanced GC cell migration in vitro and lung metastasis in vivo, whereas knockdown of circNF1 suppressed these metastatic phenotypes. Mechanistically, circNF1 was found to interact directly with IGF2BP1, thereby stabilizing HMGA2 mRNA and promoting its expression. Furthermore, ZNF460 was identified as a transcriptional activator of the NF1 host gene, which in turn upregulated circNF1 expression.DiscussionOur findings demonstrate that ZNF460-mediated upregulation of circNF1 drives GC metastasis by acting as a molecular scaffold to interact with IGF2BP1 and stabilize HMGA2 mRNA. This study not only elucidates a novel regulatory axis in GC metastasis but also identifies circNF1 as a promising prognostic biomarker and potential therapeutic target for the treatment of metastatic GC.